The Influence of Capital Structure and Profitability on Firm Value on Property and Real Estate Sector in Indonesia Stock Exchange - Umar Umar; Rasmi Nur Anggraeni; Sri Haryani (International Journal of Health, Economics, and Social Sciences (IJHESS), 2020)
The purpose of this study to determine the influence of capital structure and profitability on the firm value. This research is a quantitative descriptive research with ratio analysis based on company financial statement. The research on Property and Real Estate sector on IDX by downloading financial statement for the period 2012-2016 through IDX website (www.idx.co.id). The research population is 50 companies and based on the purposive sampling method, the number of selected samples is 28 companies. The analysis technique used is path analysis using software AMOS 21.0. The results showed that: First, simultaneously the capital structure and profitability have a positive and significant effect on firm value; Second, partially capital structure and profitability have a positive and significant effect on firm value; Third, there is a negative correlation between capital structure and profitability in its effect on firm value.